3D printed self-conformable hydrogel composites by controlling fiber alignment - Lim, Sin Yee (2018)
In recent years, 4D printing which the printed materials can transform their shape over time had been introduced and widely investigated in different research field, especially PNIPAM and NiTi 4D smart materials which had been already used in biomedical applications, such as tissue engineering, drug delivery, biosensors, and biomedical devices. One of the main challenges in 4D hydrogel printing is the printability of the material, which is the first step of fabricating mechanically stable scaffold. Besides, swelling ratio which characterized by anisotropic swelling is also the main factor to induce the 4D bending effect over time. In this study, three different polymers, which were PEGDA, alginic acid and GMHA had been screened and a programmable GMHA 4D system by introducing cellulose nanofibrils (NFC) had been developed. Comparison between three systems had been carried out with respect of various consideration such as cellulose fibril alignment and swelling ratio of the sample. GMHA had provided the best 4D printing compatibility among the materials and presented consistent bending properties after immersed in water. Relationship of the bending direction and the fiber alignment had been identified and weakness of the GMHA system was also been indicated. We can predict the final conformation of the design and achieve a target shape by investigating our system, further develops for future field use.